Dengue virus requires the CC‐chemokine receptor CCR5 for replication and infection development. Issue 4 (1st June 2015) - Marques, Rafael E.; Guabiraba, Rodrigo; Del Sarto, Juliana L.; Rocha, Rebeca F.; Queiroz, Ana Luiza; Cisalpino, Daniel; Marques, Pedro E.; Pacca, Carolina C.; Fagundes, Caio T.; Menezes, Gustavo B.; Nogueira, Maurício L.; Souza, Danielle G.; et al.
Summary Dengue is a mosquito‐borne disease that affects millions of people worldwide yearly. Currently, there is no vaccine or specific treatment available. Further investigation on dengue pathogenesis is required to better understand the disease and to identify potential therapeutic targets. The chemokine system has been implicated in dengue pathogenesis, although the specific role of chemokines and their receptors remains elusive. Here we describe the role of the CC‐chemokine receptor CCR5 in Dengue virus (DENV‐2) infection. In vitro experiments showed that CCR5 is a host factor required for DENV‐2 replication in human and mouse macrophages. DENV‐2 infection induces the expression of CCR5 ligands. Incubation with an antagonist prevents CCR5 activation and reduces DENV‐2 positive‐stranded (+) RNA inside macrophages. Using an immunocompetent mouse model of DENV‐2 infection we found that CCR5−/− mice were resistant to lethal infection, presenting at least 100‐fold reduction of viral load in target organs and significant reduction in disease severity. This phenotype was reproduced in wild‐type mice treated with CCR5‐blocking compounds. Therefore, CCR5 is a host factor required for DENV‐2 replication and disease development. Targeting CCR5 might represent a therapeutic strategy for dengue fever. These data bring new insights on the association between viral infections and the chemokine receptor CCR5.